Cation-exchange resin regeneration waste liquid as alternative NaCl source for enhancing anaerobic fermentation of waste activated sludge: Compositions of dissolved organic matters and chemical conditioning performance. (October 2020) - Pang, Heliang; Jiang, Xinxin; Li, Deqiang; He, Junguo; Yan, Zhongsen; Ma, Yingqun; Luo, Shiyi; Nan, Jun
Graphical abstract: Highlights: CRWL triggered sludge disintegration with SCOD release of 371.6 mg/g VSS. More than 96% of SCOD was composed of proteins, carbohydrates and SCFAs. Dewaterability of fermented sludge was considerably improved by FeCl3 conditioning. Performances of fermentation and conditioning were similar with CRWL and NaCl. The CRWL-enhanced strategy has numerous environmental and economic benefits. Abstract: This study reported the NaCl-enhanced anaerobic fermentation with cation-exchange resin regeneration waste liquid (CRWL) as alternative NaCl source for waste activated sludge (WAS) disposal and carbon recovery. Through 4-day CRWL-enhanced anaerobic fermentation at Na + concentration of 0.34 mol/L, the Na + -caused sludge disintegration triggered numerous release of dissolved organic matters (DOMs), i.e. 371.6 mg/g VSS, with composition distribution: acetic acid (28.2%) > butyric acid (16.1%) ≈ valeric acid (17.8%) ≈ proteins (16.4%) > propionic acid (14.4%) > unknown (3.2%) > carbohydrates (3.9%). Satisfying chemical conditioning performance for the fermented sludge was observed at the FeCl3 dosage of 0.3 g/g DS, attributing to the roles of double-layer compression and electric neutralization. The capillary suction time (CST) and sludge cake moisture content were decreased to 60.3 s and 75.1%, against those of 607 s and 93.5% before conditioning, respectively. Such "treating waste by waste" strategy could provide numerous environmental and economic benefits.